207k views
5 votes
Slove -4(x+1)-3=(x-4)

2 Answers

6 votes

Answer:


x=-(3)/(5)

Explanation:


-4(x+1)-3=(x-4) \\ \\ -4x-4-3=x-4 \\ \\ -4x-7=x-4 \\ \\ -7=5x-4 \\ \\ 5x=-3 \\ \\ x=-(3)/(5)

User Felix Olszewski
by
5.1k points
2 votes

- 4 ( x + 1) - 3 = ( x - 4)

  1. Distribute
  • - 4x - 4 - 3 = (x - 4)

2. Take away the parenthesis at the end

  • - 4x - 4 - 3 = x - 4

3. Combine like terms

  • - 4x - 7 = x - 4

4. Add 4x to each side

  • -7 = -3x - 4

5. Add 4 to each side

  • -3 = -3x

6. Divide

  • -3 / -3 = -3x / -3
  • x = 1
User N D
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.